IMPLEMENTASI MATERI “HIDUP RUKUN” MELALUI MODEL KOOPERATIF TIPE STAD PADA SISWA KELAS III - Salsabila, Zela; Mahfiroh, Riski Umi; Zahro, Rikza Fatimatuz; Mumtazah, Dzakiyatul; Hadijah, Rifa; Pangestu, Widya Trio (Jurnal Pendidikan dan Pembelajaran, 2023)
The purpose of this study was to determine the implementation of living in harmony through the STAD-type cooperative model for fourth-grade students at SDN Labang. The method used in this research is a qualitative method with descriptive research. Data collection techniques in this study include observation, interviews, and documentation. The results of this study indicate that the learning process using the cooperative model in living in harmony at SDN Labang is going well. Students can carry out learning in harmony through group work. The teacher has also been successful in implementing the STAD-type cooperative model well with students. So that students can get closer and live in harmony with their friends.